The transformative value of the Iusfeminist paradigm in Spanish universities - Gil Ruiz, Juana María (EUNOMÍA. Revista en Cultura de la Legalidad, 2023)
Aware of the University’s relevance in the training of the 21st century jurist and the importance of providing to the future legal professional the commitment and skills that incorporate the Iusfeminist gender perspective, the legislator calls for its intervention by demanding training itineraries on the prevention of violence against women and the promotion of equality between women and men. This article reflects the difficulties that this demand is now included in the mandatory compliance law and underlines the urgency that it be addressed by those who are responsible and guardians of Iusfeminist Critical Theory in Universities.